Trust networks and innovation dynamics of small farmers in Colombia: An approach from territorial system of agricultural innovation - Ramírez-Gómez, Carlos Julián; Robledo Velasquez, Jorge; Aguilar-Avila, Jorge (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
This study addresses the concepts of territorial systems of agricultural innovation and social network analysis. The general purpose of this research was analyzing a relationship between trust networks (technical, strategic and normative) and the dynamics of technological diffusion and adoption by Hass avocado farmers in each territory. To this end, two rural municipalities were compared as case studies; where 94 farmers were interviewed. A database was obtained and analyzed using a social network approach by calculating network indicators, as well as the technology adoption index (TAI) for farmers. Correlation tests were also used to determine the effect of the farmers’ trust networks on their own technology diffusion-adoption dynamics. Case studies showed that there are no significant differences in terms of technology adoption when comparing municipalities. However, the farmers’ diffusion networks show different public-private actors, as well as different degrees of input centrality and intermediation in each municipality, where correlation was found only with normative trust networks in a municipality. The capture of specific information from a geographical space is steered by the approach of territorial systems of agricultural innovation, allowing for the development of increasingly accurate strategies and interventions. Highlights This study empirically demonstrated how both technology adoption by farmers and diffusion networks have different trends across geographical spaces. The capture of specific information from a geographical space is steered by the approach of territorial systems of agricultural innovation, allowing for the development of increasingly accurate strategies and interventions. Diffusion networks of farmers from each rural municipality were built upon different actors, several of which were different and had different input centrality indicators. These actors are quite important as they are cited as intermediation indicators and sources of learning, which means they are fundamental actors in promoting greater diffusion in each territory. Trust networks (technical, strategic and normative) were found to have a different influence in each rural municipality in relation to farmers’ diffusion networks and the technology adoption index.